CONSUMPTION AS A SOCIAL STATUS SYMBOL IN STRUCTURALISM - N. D. Naydenov (Science and Innovation Center Publishing House, 2014)
The article looks at the basic theoretical concepts of the political economy of the sign (structuralism, postmodernity) and their development in the theory of power based on the work by J. Baudrillard ‘For a Critique of the Political Economy of the Sign’. The study is focused on consumption as the person’s social status symbol, it compares and contrasts basic concepts of structuralism and neo-liberalism. According to structuralism social structure is reproduced through the reproduction of objects/signs. It is important that not only things or money but mathematical formulas, linguistic constructions and people can act as signs. Structuralism views consumption as a person’s social status symbol. Respectively, exchange is viewed as the exchange of symbols.  The society needs the diversity of signs and manipulating the signs is one of the modern society’s illnesses. Liberalism is a social movement, which confronts the person’s enslavement by communal ties and limitations within the limits of property and in the aspects where the individual is helpless in front of the society. Neoliberalism proclaims the liberal model of an individual, who is primarily concerned with their belonging to their society and the struggle between the signs is significant. Assigning a certain value to the symbol is typical both for structuralism and neo-modernism. The authors find it necessary to raise the symbolic diversity of the Russian society trough increasing the forms of consumption. At the same time we should not forget that the society is based on material production.